Central Role of Gimap5 in Maintaining Peripheral Tolerance and T Cell Homeostasis in the Gut - Mehari Endale; H. Ibrahim Aksoylar; Kasper Hoebe (Mediators of Inflammation)
Inflammatory bowel disease (IBD) including Crohn’s disease and ulcerative colitis is often precipitated by an abnormal immune response to microbiota due to host genetic aberrancies. Recent studies highlight the importance of the host genome and microflora interactions in the pathogenesis of mucosal inflammation including IBD. Specifically, genome-wide (GWAS) and also next-generation sequencing (NGS)—including whole exome or genome sequencing—have uncovered a large number of susceptibility loci that predispose to autoimmune diseases and/or the two phenotypes of IBD. In addition, the generation of “IBD-prone” animal models using both reverse and forward genetic approaches has not only helped confirm the identification of susceptibility loci but also shed critical insight into the underlying molecular and cellular pathways that drive colitis development. In this review, we summarize recent findings derived from studies involving a novel early-onset model of colitis as it develops in GTPase of immunity-associated protein 5- (Gimap5-) deficient mice. In humans, GIMAP5 has been associated with autoimmune diseases although its function is poorly defined. Here, we discuss how defects in Gimap5 function impair immunological tolerance and lymphocyte survival and ultimately drive the development of CD4+ T cell-mediated early-onset colitis.